MENINGKATKAN PARTISIPASI SISWA KELAS 4A SDN 44 AMPENAN PADA MATA PELAJARAN MATEMATIKA DENGAN MENGGUNAKAN MEDIA INTERAKTIF - Putri Widnyani, Ni Wayan; Ahmad Busyairi; Novalia Andriyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to improve the active participation of 4A grade students at SDN 44 Ampenan in mathematics learning through the use of interactive media. The main issue addressed is the low student participation due to mathematics being perceived as a challenging and less engaging subject. This study employs a Classroom Action Research (CAR) approach conducted in two cycles. In the first cycle, learning activities were carried out without using interactive media, and observations showed that only 60% of students were actively involved. In the second cycle, interactive media, such as digital games like Wordwall and Spin the Wheel, were utilized to enhance student engagement, resulting in a significant increase in participation to 87%. The findings indicate that interactive media effectively enhance student participation and help them understand mathematical concepts more enjoyably. Therefore, the use of interactive media can be applied to create more engaging and effective learning experiences.